Pengaruh profitabilitas, likuiditas, dan struktur aset terhadap struktur modal sektor consumer non cyclicals - Febrianti, Salsabella Cendy Amalia; Wuryani, Eni (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The focus of this research is to identify the effect of profitability, liquidity, and asset structure on capital structure. The study population is the consumer noncyclical sector which is listed on the Indonesian Stock Exchange (IDX). The sample was selected using a purposive sampling technique. The data collection methodology is non-participant observations taken from 2020 – 2022 financial reports. The analytical method used in the study is multiple regression analysis. Profitability is determined by the return on asset, liquidity by the current ratio, asset structure by fixed asset ratio, and capital structure by debt to equity ratio. The result of this study indicates that partial profitability does not affect capital structure, liquidity and asset structure have a significant negative impact on capital structure. Profitability, liquidity, and asset structure simultaneously affect the capital structure by 35,4%.